Regulacija naboja in robni pogoji v elektrostatiki - Koncilja, Maks (Matrika, 2024)
Some macromolecules can donate and accept acidic and basic groups. The charge regulation depends of pH value and local potential, it affects some natural processes, such as the passage of DNA through nanopores. Charge regulation is exploited in industry, including the production of polyelectrolyte materials. In this paper, charge regulation is introduced with “chemical” phenomenological interpretation and a “physical” statistical mechanical approach. Introduction of the charge regulation is followed by the description of charge regulated macromolecules in an ion solution, starting with the example of two charge regulated macromolecules. The final part focuses on the many-body problem of macromolecules, which can be described differently based on the physical circumstances. When dealing with static macromolecules the cell model is used, whereas under alternative conditions a collective approach of moving macromolecules is utilized.
Keywords: charge regulation; electrostatics; elektrostatika; macromolecules; makromolekule; regulacija naboja; titracija; titration